In vivo storage of oocytes leads to lower survival, increased abnormalities and may affect the ploidy status in the yellowtail tetra Astyanax altiparanae - Nascimento, Nivaldo Ferreira do [UNESP] (2018)
In this study we analyzed whether the in vivo storage of oocytes (time after ovulation until fertilization) affects the survival and the ploidy status of the yellowtail tetra Astyanax altiparanae. Fish were induced to spawn and, after ovulation, a small aliquot was stripped and immediately fertilized (positive control group). Subsequently, aliquots (similar to 150 oocytes) were stripped and fertilized at various time points of 60, 120, 180 or 240 min. Developmental stages, abnormalities, survival and the ploidy status of the hatched larvae were examined. As expected, in the control group, 100% of the larvae were diploid. Conversely, triploid individuals were observed just at the 60 min treatment time point (0.6%). In vivo storage of oocytes also influenced the survival rates (P < 0.05); the 180 and 240 min samples, respectively, presented lower survival rates at gastrula (50.10 +/- 6.26% and 40.92 +/- 5.32%), and somite (17.80 +/- 5.14% and 4.41 +/- 2.76%) stages and lower hatching rates (12.01 +/- 4.04% and 4.41 +/- 2.76%). A higher percentage (99.27 +/- 0.40%) of normal larvae and only a few abnormal larvae (0.73 +/- 0.40%) were observed in the control group (P = 0.0000). This observation did not differ from that observed at the 60 min treatment point (P = 0.9976). A significant increase in the percentage of abnormalities was observed in the other treatments, and, after 240 min, the highest percentage of abnormal larvae was seen (P=0.0024; 83.33 +/- 16.67%). In conclusion, we showed that oocyte ageing had a significant effect on survival and may affect the ploidy status in A. atiparanae.